Attitudes and behaviors of society towards women with substance use disorder - Yılmaz Tuncel, Gözde; Şaşman Kaylı, Derya; Yararbaş, Görkem (Journal of Dependence, 2023)
Objective: The aim of this research is to determine the attitudes and behaviors of the society towards women illicit substance use and to examine the relationship between these attitudes and sociodemographic variables. Method: The population aged 18 and over was included in the study, which was carried out in a cross-sectional type with a quantitative method. In addition to sociodemographic questions, a questionnaire about attitudes towards women using addictive substances and the Attitudes and Behaviors Scale for Individuals Using Addictive Substances (BYMT) were used. The study was conducted online with 410 people reached through Google Forms and of the participants were 50% female and 50% male. Results: Men have more negative attitudes and thoughts towards women who use illegal substances, negative attitudes decrease as the level of education increases, and people living in villages or towns until they reach the age of 18 have higher negative attitudes than people living in the province. In addition, participants who have negative attitudes towards individuals who use illegal substances are more likely to agree that women using illegal substances deserve violence, they are difficult to be treated, and men’s use of illegal substances is more acceptable. Conclusion: Stigmatizing attitudes and behaviors towards female addicts may reduce the visibility of women in the field of substance use and adversely affect the process of applying for treatment. The implementation of community-based studies and psychosocial treatment processes that consider gender differences will support the struggle against substance addiction.